PENEGAKAN HUKUM PIDANA YANG DILAKUKAN PENYIDIK PEGAWAI NEGERI SIPIL DIREKTORAT JENDERAL BEA DAN CUKAI TIPE MADYA PABEAN B KOTA PEKANBARU DALAM UPAYA PENANGGULANGAN LIQUID ILLEGAL TANPA PITA CUKAI - Novendi Jaya Putra Purba; Maria Maya Lestari; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The case regarding liquid excise took place at the Regional Office of the Directorate General of Customs and Excise, Pekanbaru City Type B, where they destroyed the results of the customs and excise action in the parking lot. One of the illegal products that were destroyed was liquid vape or e-cigarettes. During the last three years, Customs and Excise took 838 actions related to 6,580 illegal liquid bottles with the value of goods resulting from prosecution reaching Rp 1.5 billion.This type of research can be classified in the type of sociological (empirical) legal research. However, although there is an element of field research (Sociological) in this study, the data analysis method is carried out with a qualitative approach, because the dominant data used is secondary data or library data with field data as a complement. This research was conducted in the jurisdiction of the Directorate General of Customs and Excise, Type B Intermediate Customs, Pekanbaru City.The conclusions that can be obtained from the results of the study are First, Law enforcement carried out by the Pekanbaru City Customs and Excise is still controlling and is designed to reduce the circulation of illegal liquids because so far the perpetrators of the crime of excise bands have not been followed up to the examination process at court. Even though the criminal acts of illegal liquid circulation without excise stamps for the perpetrators and even liquid traders have fulfilled the elements of offense contained in Law Number 39 of 2007 concerning Excise. Second, the obstacle in law enforcement of illegal liquid circulation without excise in Pekanbaru City is the lack of tips that improve the eradication of illegal liquid circulation, such as providing punishment according to the provisions of the excise law so that it can ensnare perpetrators and create a deterrent effect.Keywords: Policy, Criminal Law, Sexual Violence, Chemical Castration, Criminalization.